General Cultural Competence of a Future Teacher in a Changing World - O. R. Neradovskaya; V. A. Starodubtsev (Открытое образование (Москва))
The purpose of the study. The paper analyzes the content оf the concept of “general cultural competence of a future teacher” and its dialectical development in a changing world under the influence of various factors: the new technological order; the complexity and diversity of various social environments; the risks of environmental, energy and epidemic crises; the emergence of artificial intelligence and learning neural networks; and the large consequences of small (at first glance) events in public life. The authors of this paper identified the inseparable connection of the general cultural competence of a future teacher with the general culture of human society. The work culture (professional activity) of a teacher is understood as an intellectual, socially oriented creative activity in the field of education, which has a spiritual ground and value sense. Such professional activity includes imperatives of personal and professional development, learning new things, motivation to participate in the life and upbringing of the subjects of their work – students. The trend of pragmatism in the development of educational programs of higher education, underestimation of the humanistic function of pedagogical universities and the need to form longitudinal professional and life goals of graduates is actualized. Materials and methods. The study is based on the analysis of scientific publications in the field of competence-based, culturological and learner-centered approaches in pedagogy. The content of publications was compared, and the frequency of key terms in these publications was analyzed using the online service “Semantic text analysis online, seo text analysis”.The results of the study. The results prove that the phenomenon of culture arises in the process of human coevolution. In this study, the structure and content of culture is seen as a sphere with three poles (religion, art, science). In the process of historical increase in the volume of culture, these poles could have changed mutual distances, demonstrating a prevailing influence of each pole on the volume of the culture sphere. Furthermore, the series of categories of “cult – culture – general cultural competence of a future teacher” was analyzed. In the context of the competency-based approach, an analysis of the content of the concept “general cultural competence of a future teacher” is considered. It has been suggested that leadership competence can be considered as part of the general cultural competence of a future teacher, determining the ability to independently organize his or her own professional and life trajectory from the position of a leader, creating an atmosphere of cooperation in the pedagogical, design or research process. The leader's worldview is seen to be an integral part of the general culture of a person, being realized in the normative (regulatory) and evaluative (axiological) functions of the culture, as well as in the socialization function together with a continuous desire for self-improvement in the profession and life.Conclusion. The findings of the study demonstrate that teachers, as carriers and subjects of culture, need to develop their general cultural competence to navigate in and adapt to a changing world. The considered competences are crucial in the modern conditions and should be directly or indirectly introduced into the future Federal State Educational Standards of Higher Education in the Russian Federation.